Pengaruh Pupuk Organik COSIWA dan Pupuk Anorganik NPK pada Perkembangan Tanaman Kangkung Ditinjau dari Suhu Tanah - Listyaningrum, Trisna Avi; Toifur, Moh. (Sekolah Tinggi Pertanian Kutai Timur, 2023)
The use of inorganic fertilizers will provide hotter temperatures than using organic fertilizers. The higher nutrient content causes this in inorganic fertilizers than in organic fertilizers. High and low soil temperatures will affect plant growth; the higher the soil temperature, the faster the growth of plants. This study aims to analyze the results of developing water spinach plants grown using COSIWA liquid organic fertilizer and NPK liquid inorganic fertilizer. The design of this study was the measurement of soil temperature and plant height based on soil depth in organically fertilized soils using COSIWA and inorganic fertilizers using liquid NPK. The data generated were measurements of soil temperature for 12 hours and observations of plant stem length, leaf color, stem condition, and plant freshness for four weeks. This study showed that water spinach plants grown using COSIWA liquid organic fertilizer had a lower soil temperature of 32.2 oC compared to kale plants grown using NPK liquid inorganic fertilizer, namely 32.2 oC. In addition, the growth of water spinach plants grown using COSIWA liquid organic fertilizer and water spinach plants grown using liquid inorganic fertilizer NPK showed almost the same growth results as seen from the observations on plant length, leaf condition, stem condition, and plant freshness. Keywords: COSIWA organic fertilizer, kangkung plants, NPK inorganic fertilizer, soil temperature